Afro-Catholic Baptism and The Articulation of a Merchant Community, Agoué 1840–1860. (12th May 2015) - Parés, Luis Nicolau
Abstract: This paper analyzes the "Southern" Afro-Brazilian Catholicism which was brought to West Africa by former slaves from Brazil prior to the expansion of the "Northern" European Catholic missions. In examining two significant mass baptisms held in the town of Agoué in 1846 and 1855, this paper explores the religious history of the Aguda or Afro-Brazilian freed slaves, and how they built a network of ethnic, commercial, and affective relationships by means of Catholic baptism and godparenting. The Aguda's Catholic affiliation (rather than conversion), beyond being coextensive with Brazilian identity, served to produce a merchant community whose main activity, in the early period, was the slave trade. The paper also discusses the methodological potential of cross referencing and fertilizing West African data with Bahian data in order to elucidate how the returnees' appropriation of Catholic ritual was shaped by their previous Brazilian experience. Résumé: Cet article analyse le catholicisme afro-brésilien du "sud" apporté en Afrique de l'ouest par les anciens esclaves brésiliens avant même l'expansion des missions catholiques du "nord" venues d'Europe. Grâce à l'étude de deux baptêmes en masse effectués dans la ville d'Agoué en 1846 et 1855, cet article explore à la fois l'histoire religieuse des Agudas, les anciens esclaves afro-brésiliens, et la construction de leur réseau de relations ethniques, commerciales et personnelles à travers le baptême catholique et le parrainage religieux. L'affiliation catholique des Agudas (plus que leur conversion) co-existante à leur identité brésilienne, a contribué à la création d'une communauté de marchands dont l'activité principale était, dans ses premières années, la traite des esclaves. Ce papier se penche aussi sur le potentiel méthodologique de croiser les sources ouest-africaines et celles de Bahia afin d'éclairer la manière dont les Agudas se sont appropriés un rituel catholique façonné par leur expérience brésilienne.